Simulated impact of vitamin A-fortified sugar on dietary adequacy and association of usual sugar intake with plasma and breast milk retinol among lactating Zambian women - Haile, Demewoz; Engle-Stone, Reina; Caswell, Bess; Luo, Hanqi; Dodd, Kevin W.; Arnold, Charles D.; Jobarteh, Modou; Greene, Matthew; Chipili, Mackford; Haskell, Marjorie J.; Palmer, Amanda C. (Wiley, 2025)
In Zambia, mandatory sugar fortification with vitamin A (VA) has been implemented, but its impact on VA inadequacy and status has yet to be assessed. This study evaluated the contribution of VA-fortified sugar to dietary VA adequacy and the relationship between dietary intakes and VA status in 243 lactating women, based on 24-h dietary recalls in Mkushi, Zambia. We estimated usual intake distributions and the prevalence of VA adequacy using the National Cancer Institute (NCI) method across five scenarios: without sugar fortification; with fortification at 3.1 or 8.8 mg/kg (median levels previously measured in Mkushi); at 10 mg/kg (the minimum legal requirement at the household level), and at 15 mg/kg (the minimum legal requirement at the factory level). We applied the regression calibration method to examine associations of usual intake of sugar and dietary VA with plasma and breast milk retinol concentrations. Without fortified sugar, the estimated prevalence of dietary VA inadequacy was 83% (standard error [SE]: 6). Projected reductions in VA inadequacy were 7 (SE: 6), 24 (SE: 14), 30 (SE: 15) and 47 (SE: 18) percentage points for sugar fortification at 3.1, 8.8, 10 and 15 mg/kg, respectively. Usual sugar intake was not significantly associated with plasma or breast milk retinol concentrations. The potential impacts of sugar fortification on VA intakes are limited if the programme is not implemented as planned. Even if the target fortification levels are achieved (10 mg/kg), sugar fortification alone is unlikely to eliminate dietary VA